Case Studies of Comprehensive Gas Control Method during Fully Mechanized Caving of Low-Permeability Ultrathick Coal Seams. (22nd July 2021) - Jiang, Bangyou; Gu, Shitan; Li, Wenshuai; Zhang, Guangchao; Zhang, Jihua
Abstract : Slicing fully mechanized caving mining is a standard high-efficiency mining method for ultrathick coal seams. However, the effectiveness of gas control has accentuated the difficulty in fully mechanized top coal caving of low-permeability ultrathick coal seams. This study focused on mining the No. 9-15 coal in Liuhuanggou Coal Mine, Xinjiang Province, China. To this aim, the results of theoretical analyses and field tests were combined to explore a comprehensive gas control method for fully mechanized caving of low-permeability ultrathick coal seams. The No. (9-15)06 panel was a top-slicing panel of the No. 9-15 coal with a mining height of 9 m. Gas analysis results revealed that gas emissions in the No. (9-15)06 panel are mainly sourced from the coal wall, caving top coal, goaf, and neighboring coal seams. Based on gas source separation, a comprehensive gas control method was proposed. The proposed method was based on the combination of gas predrainage alongside the coal seam, high-position drilling on the top, preburial of pipes in the goaf, and pressure-balancing ventilation. The permeability and gas predrainage were enhanced by hydraulic fracturing in low-permeability coal seams. According to the characterizations of coal seam and crustal stress distribution, the arrangement of the boreholes and backward-segmented fracturing technology were designed. From the field results, the coal seam presented a remarkable prefracturing under hydraulic fracturing. Besides, the mean gas predrainage from the boreholes was enhanced by four times compared to the prehydraulic fracturing state. Finally, using the proposed comprehensive control method based on the gas sources, field tests were performed in the No. (9-15)06 panel. The measured results demonstrated that gas concentration in the return airflow is fluctuated within a range of 0.05% to 0.35%. The proposed gas control method can provide an insightful reference for other similar projects.